Personal characteristics and level of management as determinants of the conceptual skills of academic librarians in Quezon City - Peza, Judith O. (2003)
Management is very essential in every organization. In a library setting, management is one of the important factors that makes it function. Management has three levels, the top, middle and the low management wherein in each level, it has different functions. The top management should have greater conceptual skills in order for it to perceive the future of the library. The people in this level must have the ability to think beyond time to be able to make the library more effective. The middle level management should have the same quantity of conceptual skills and technical skills. On the other hand, the low management level should have greater technical skills because their job is mostly hands-on.